Construction of an expression vector carrying gene coding mannitol-1-phosphate dehydrogenase (mtlD) from Escherichia coli JM109 strain to transfer into maize - Viet, Le Bac; Lien, Nguyen Thi Kim; Hoang, Nguyen Huy; Hai, Nong Van; Hue, Huynh Thi Thu (Academia Journal of Biology, 2016)
Maize (Zea mays L.) is one of the important cereal crops in the world, and the maize demand is increasing but the productivity and yield of maize have been affected by extreme adverse conditions, of tghose drought is one of the main factors reducing productivity due to inhibition of growth and decreasing photosynthesis in plants. Mannitol-1-phosphate dehydrogenase (mtlD) is an enzyme that catalyzes the conversion of fructose 2- and 6-phosphate to mannitol-1-phosphate in the photosynthesis pathway of plants. To produce maize containing mtlD gene to increase the height, fresh and dry weight, salt/drought tolerance in host plant based on accumulation of mannitol, we constructed an expression vector carrying the mtlD gene. The mtlD gene was isolated from E. coli JM109, cloned and sequenced in vector pJET1.2. This sequence was then optimized by OptimumGeneTM software to make it appropriate into plants. The modified gene was recombined into a mediate pRTRA vector containing 35S promoter and 35S terminator, the 35Spro::mtlD::35S cassette was construced into pCAMBIA1300 Ti-plasmid. The new recombinant vector was transformed into A. tumefaciens which could be used as a material for maize transformation. Citation: Le Bac Viet, Nguyen Thi Kim Lien, Nguyen Huy Hoang, Nong Van Hai, Huynh Thi Thu Hue, 2017. Construction of an expression vector carrying gene coding mannitol-1-phosphate dehydrogenase (MTLD) from Escherichia coli JM109 strain to transfer into maize. Tap chi Sinh hoc, 39(1): 61-67. DOI: 10.15625/0866-7160/v39n1.7073. *Corresponding author: hthue@igr.ac.vn Received 30 December 2015, accepted 20 March 2017